Analisis Peran Stakeholder terhadap Pembangunan Berkelanjutan Agrowisata Anggur Desa Sanggalangit Kabupaten Buleleng - Ni Putu Cahaya Putri; I Made Endra Kartika Yudha (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the role of stakeholders in the sustainable development of grape agrotourism in Sanggalangit Village, Buleleng Regency. The village is recognized as one of the largest grape-producing regions in Bali and holds significant potential for agrotourism development. The research employs a quantitative approach, utilizing Focus Group Discussions (FGD) and data analysis through the MACTOR method (Matrix of Alliances, Conflicts, Tactics, Objectives, and Recommendations). The study involves six key stakeholder groups: the Tourism Office, Agriculture Office, Village Government, Agrotourism Managers, Grape Farmers, and the Local Community. The analysis reveals varying levels of influence and dependence among actors in relation to different development objectives, with certain stakeholders occupying strategic positions in determining the direction of agrotourism sustainability. The most widely supported objectives include increasing income, productivity, and tourism promotion. Stakeholder involvement plays a crucial role in addressing production challenges and creating inclusive, sustainable agrotourism. This study contributes theoretically to stakeholder analysis and offers practical insights for community-based agricultural tourism policy development.